Ninjin'yoeito Alleviates Neuropathic Pain Induced by Chronic Constriction Injury in Rats - Takemoto, Risa; Michihara, Seiwa; Han, Li-Kun; Fujita, Nina; Takahashi, Ryuji (Frontiers in Nutrition, 2021)
Kampo medicines are frequently used empirically to treat pain in clinical practice. Ninjin’yoeito (NYT), which is associated with few adverse effects, is often used to treat the elderly, but has not yet been examined in detail. We herein investigated the effects of NYT, at 500 and 1,000 mg/kg p.o.(NYT500/NYT1000 group) in single and repeated administrations for 14 days, on pain in rats with peripheral neuropathy induced by loose ligation of the sciatic nerve (chronic constriction injury: CCI). Untreated CCI rats given distilled water were used as a contol group. To assess induced pain, the pain threshold was measured using the von Frey test. To evaluate spontaneous pain, the ground-contact area of the paw with neuropathic pain was measured using the Dynamic Weight Bearing test. Serum samples were collected after the test to elucidate the mechanism of action of NYT, and brain-derived neurotrophic factor (BDNF) and corticosterone protein levels, which have been reported to change due to chronic pain, were analyzed. After single administration of NYT, the pain threshold rose in the NYT500 and NYT1000 groups. The pain threshold tended to rise on day 14 of repeated administration in the NYT500 group (p=0.08) and it significantly rose at NYT1000 group (p<0.05) compared to Control group. In addition, the foot contact area increased (p=0.09). Therefore, CCI-induced pain was significantly remitted and spontaneous pain was remitted after repeated administration of NYT. Serum BDNF levels were higher in untreated CCI rats than in normal rats (p = 0.05), but decreased after the repeated administration of NYT (NYT1000, p = 0.15), while serum corticosterone levels were lower (p = 0.12) than those in normal rats and increased after the repeated administration of NYT (NYT1,000, p = 0.07). The blood BDNF level has been suggested to influence pain intensity. The findings demonstrated NYT effectively treats neuropathic pain, suggesting that a NYT-induced decrease in blood BDNF contributed to the mechanism of pain relief. In addition, the variation of corticosterone was observed, suggesting that normalization of responsiveness to stress by NYT contributed to the pain relief.